Successful switching from risperidone to cariprazine in a schizophrenic patient with pronounced functional deficit. Case report - Sahlsten Schölin, Johan; Rodriguez Cruz, José; Hjorth, Stephan (Frontiers in Psychiatry, 2023)
A 22-year-old male was admitted to an in-patient psychiatric unit for treatment, after a period of 2 years of increasing psychotic symptoms corresponding to a very severe case of schizophrenia across the entire scale of symptom disorder domains along with some drug abuse comorbidity. Previous treatments with olanzapine (OLA) and risperidone (RIS) had been at best partly successful towards his positive symptoms with no, or even worsening effects on the negative symptomatology. Given the gravity of the latter symptoms and functional impairment of our patient, he might thus have been a candidate for clozapine (CLZ) treatment. It was however decided to switch his antipsychotic treatment to cariprazine (CAR), an agent with a novel pharmacological and clinical profile, because of its favourable pharmacodynamic, pharmacokinetic, and tolerability/safety properties. In a follow-up on the patient 6 months after discharge he is not fully recovered, but the recovery attained reflects a marked functional improvement compared to before the RIS-to-CAR switch. The remarkable response to CAR observed may, speculatively, be in line with the suggestion that CAR could offer an alternative, safer, and more tolerable monotherapy approach (vs. CLZ) for patients with severe negative symptoms and functional deficiency resistant to standard antipsychotic treatment. He appears to occasionally still be taking drugs, but no worsening of positive symptoms has been noted. Whether or not he could reach full recovery if he would abstain entirely from drugs of abuse remains an open question.